2005
DOI: 10.1007/s00204-005-0669-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lung resistance-related protein, LRP, and multidrug resistance-related protein, MRP1, in normal human lung cells in long-term cultures

Abstract: Transport processes form part of the body's defense mechanism, and they determine the intracellular levels of many endogenous and exogenous compounds. The multidrug resistance-related protein MRP1 and the lung resistance-related protein LRP are associated with drug resistance against chemotherapeutics; they protect cells against toxic compounds. There is much experimental evidence to suggest that both of these transporter proteins serve important physiological functions. The expression of LRP and MRP1 was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Furthermore, the protein expression amounts of OCTN1 and OATP2B1 in lung tissue exhibit almost the same as that in primary cultured cells, suggesting that these primary cultured cells could reflect in vivo transport function. In support of this notion, it has been reported that MRP1 protein expression levels were stable after 20 weeks of culture time in NHBE subpassages 54. In contrast, there has been emerging evidence that the expression levels of OATPs are downregulated in primary cultured hepatocyte of human and rat than those in liver tissues 55,56.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the protein expression amounts of OCTN1 and OATP2B1 in lung tissue exhibit almost the same as that in primary cultured cells, suggesting that these primary cultured cells could reflect in vivo transport function. In support of this notion, it has been reported that MRP1 protein expression levels were stable after 20 weeks of culture time in NHBE subpassages 54. In contrast, there has been emerging evidence that the expression levels of OATPs are downregulated in primary cultured hepatocyte of human and rat than those in liver tissues 55,56.…”
Section: Discussionmentioning
confidence: 95%
“… 39 41 A host of cisplatin-resistant proteins have been reported, for instance, LRP, MRP2, and breast cancer resistance protein. 36 , 42 , 43 LRP is overexpressed in several non-P-glycoprotein cancer cell lines with performance of MDR. 44 LRP is a small subcellular structure located at cytoplasmatic vaults that may be in charge of subsequent exocytosis of agents from the cell.…”
Section: Discussionmentioning
confidence: 99%
“…23 MRP1 was reported to be expressed both at the mRNA and protein level in undifferentiated NHBE and normal alveolar lung cells grown on cell culture dishes, with nevertheless high intra-individual variations. 44,66 The functionality of the transporter in normal lung cells was demonstrated by the decreased efflux of the MRP substrate carboxydichlorofluorescein (CDF) in presence of the MRP inhibitor MK-571. 44 Immunodetection of MRP1-5 in undifferentiated NHBE and alveolar cells showed that MRP1 and MRP3 were localised in the cell membrane while MRP2, MRP4 and MRP5 were intracellular proteins.…”
Section: Mrps In Respiratory Cell Culture Models In Vitromentioning
confidence: 99%